Diagnostic Yield of Cytologic Analysis of Pericardial Effusion in Dogs. (16th November 2013) - Cagle, L.A.; Epstein, S.E.; Owens, S.D.; Mellema, M.S.; Hopper, K.; Burton, A.G.
<x xml:space="preserve">Abstract</x> Background Pericardial effusion cytology is believed by many to be of limited value, yet few studies have evaluated its diagnostic utility. Objectives To determine the diagnostic utility of cytologic analysis of pericardial effusion in dogs and to determine if consideration of additional data could improve the diagnostic yield. Animals Two hundred and fifty‐nine dogs with cytologic analysis of pericardial effusion performed between April 1990 and June 2012. Methods Electronic medical records from a university teaching hospital were retrospectively reviewed; signalment, complete blood count, serum biochemistry, cytologic analysis of pericardial effusion, and echocardiographic data were recorded. Cytology was classified as diagnostic (infectious or neoplastic) or nondiagnostic (hemorrhagic or other) and groups were compared with multiple Student's t‐tests. Results Cytology was grouped as nondiagnostic (92.3%) or diagnostic (7.7%) and characterized as hemorrhagic (90%), neoplastic (4.6%), infectious (3.1%), or other (2.3%). Overall cytologic analysis of pericardial effusion diagnostic utility was 7.7% and increased to 20.3% if the effusion hematocrit (HCT) <10%; echocardiographic evidence of a mass did not result in a significant increase in the diagnostic utility. Conclusions and Clinical Importance The diagnostic utility of cytologic analysis of canine pericardial effusion is variable depending on the underlying etiology. In this group of dogs, the diagnostic yield of cytologic analysis was greater for pericardial effusion samples in which the HCT was less than 10%.